Cinema year by year, 1894-2005 - Bergan, Ronald; Finler, Joel W., (Joel Waldo); Karney, Robyn (New York : DK, 2005)
A chronological compilation of over 100 years of film and movie history from 1894 to 2005 containing thousands of entries, stills, studio portraits, and key events and facts from each year including Academy Award winners.
Includes indexes.
Adult
Keywords: Motion pictures -- History -- Chronology; Motion pictures -- History -- Pictorial works; Motion pictures -- History -- Chronology; Motion pictures -- History -- Pictorial works